The Implementation of Castration as an Additional Punishment Imposed on Perpetrators of Sexual Harassment in Indonesia - Sibarani, Sinintha Yuliansih; Lazuardhany, Mutia (Dinasti Research, 2026)
The Implementation of Castration as an Additional Punishment Imposed on Perpetrators of Sexual Harassment in Indonesia discusses the phenomenon of increasing sexual violence cases, which highlights the urgency of strengthening the criminal justice system. This research aims to analyze the legal basis, objectives, and implementation of chemical castration within Indonesia’s criminal law system. The research method employed is normative juridical, using statutory and conceptual approaches through the analysis of legislation, court decisions, and academic literature. The findings indicate that chemical castration is regulated under Law Number 17 of 2016 and Government Regulation Number 70 of 2020 as an additional punishment for perpetrators of sexual violence against children. Its application is based on the combined theory of punishment, which emphasizes aspects of retribution, deterrence, and rehabilitation. In conclusion, although chemical castration possesses legal legitimacy and preventive objectives, its implementation still faces ethical, medical, and constitutional challenges that must be addressed to ensure its effective enforcement.